2013
DOI: 10.1194/jlr.m041954
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol lowering drug may influence cellular immune response by altering MHC II function

Abstract: There is a report that lowering of membrane cholesterol decreases expansion of the immune repertoire of CD4 + T cells, but not CD8 + T cells, in the thymic organ culture ( 3 ). The association of MHC II with either lipid raft or tetraspanin membrane domain is essential for effective antigen presentation ( 4,5 ). The treatment of antigen-presenting cells (APCs) with methyl ␤ -cyclodextrin (m ␤ -CD), known to deplete cellular cholesterol ( 6 ), reduces the antigen-presenting ability of MHC II without altering ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 63 publications
4
36
0
Order By: Relevance
“…The Ada-mediated enhancement of T cell responses by I-MFs could be explained on the basis of a favorable peptide exchange at the MHC-II molecule. Previously, we showed that there is a significant decrease in membrane cholesterol in L. donovani-I-MFs (56), and the transmembrane domain of MHC-II interacts with cholesterol with high affinity (K D 47 nM) (34). Our study also showed that depletion of membrane cholesterol alters conformation of MHC-II that leads to reduced p-MHC-II complex formation (34).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The Ada-mediated enhancement of T cell responses by I-MFs could be explained on the basis of a favorable peptide exchange at the MHC-II molecule. Previously, we showed that there is a significant decrease in membrane cholesterol in L. donovani-I-MFs (56), and the transmembrane domain of MHC-II interacts with cholesterol with high affinity (K D 47 nM) (34). Our study also showed that depletion of membrane cholesterol alters conformation of MHC-II that leads to reduced p-MHC-II complex formation (34).…”
Section: Discussionsupporting
confidence: 61%
“…Previously, we showed that there is a significant decrease in membrane cholesterol in L. donovani-I-MFs (56), and the transmembrane domain of MHC-II interacts with cholesterol with high affinity (K D 47 nM) (34). Our study also showed that depletion of membrane cholesterol alters conformation of MHC-II that leads to reduced p-MHC-II complex formation (34). It is possible that decreases in membrane cholesterol in L. donovani infection alters the conformation of MHC-II, which may contribute to the defective p-MHC-II complex formation when intracellular parasite numbers are high.…”
Section: Discussionmentioning
confidence: 97%
“…To further investigate the mechanism involved in lytic activity, we investigated the potent role of lipid rafts of the effector cells. Indeed numerous proteins essential to the lytic mechanism are integrated into lipid rafts (Razzaq et al, ; Roy et al, ) just as leptin receptor (Frühbeck et al, ; Tu et al, ). Our results showed for the first time on primary spleen cells that cholesterol depletion reduces lytic activity by 31%.…”
Section: Discussionmentioning
confidence: 99%
“…Human leukocyte antigen (HLA)‐II molecules have a key role in T lymphocytes activation and immune response hemostasis. Statins directly inhibit IFN‐γ‐induced expression of HLA‐II, and therefore act as a direct inhibitor of HLA‐II‐mediated T cell activation . This effect of statins is mediated by suppression of the inducible promoter IV of the HLA‐II transactivator CIITA, which is found in different cells of the immune system, such as monocyte and endothelial cells .…”
Section: Therapeutic Approachesmentioning
confidence: 99%